Educational Communication of Prospective Teachers as a Reinforcement of the Integration of Mathematics and Islamic Education - Afifah Nurwahidah; Haniyah Shaffina Alfath; Lukmanul Akhsani (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study aims to investigate the communication processes employed by prospective teachers when integrating Islamic values into mathematics education, identifying effective tactics, patterns, challenges, and supporting factors to address gaps in prior research that focused mainly on student outcomes rather than teacher dynamics. The methodology involves a qualitative approach through systematic content analysis of academic journals, books, and relevant documents published between 2015 and 2025, sourced from databases such as Google Scholar and Garuda using targeted keywords like "prospective teacher communication" and "Islamic mathematics integration," with data thematically classified and interpreted via educational communication theories. Key findings highlight successful strategies including interactive dialogue, religious narratives, critical reflection, and technology-based media rooted in Islamic principles, which significantly boost student motivation, conceptual understanding, and character development; however, persistent challenges such as insufficient specialized training, limited appropriate learning resources, time constraints, and socio-cultural variations hinder implementation, though institutional support, contextual modules, and teacher enthusiasm serve as vital enablers.